2018
DOI: 10.2217/rme-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Perinatal Stem Cells Research: a Precious Cell Source for Clinical Applications

Abstract: Perinatal tissues possess numerous types of stem (stromal) cells, which are considered effective candidates for cell therapy. These tissues possess common characteristics of both embryonic and adult stem cells, and cell therapists have begun to use perinatal stem cells to treat several diseases. Despite their benefits, these cells are considered biological waste and usually discarded after delivery. This review highlights the characteristics and potential clinical applications in regenerative medicine of perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 133 publications
0
32
0
1
Order By: Relevance
“…MSCs produce exosomes that contain growth factors, mRNA, microRNA and mitochondrial companents. This content ensures that the exosomes are long-acting [42][43][44].. MSCs are nonhematopoietic multipotent stromal cells that can be isolated from different sources, including bone marrow, adipose tissue, umbilical cord tissue, cord blood, placenta, dental pulp and amniotic fluid [12,45,46]. Umbilical cord Wharton's jelly derived mesenchymal stem cells (WJ-MSCs) are superior to other cell types in retinal degeneration in terms of how easily we can obtain these cells, as well as their tissue compatibility, rapid proliferation, long-term efficacy in the transplanted tissue, high paracrine effect, immunomodulation effect, non-tumoral side effect, and because these cells have similar features as the retinal pigment epithelium [13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs produce exosomes that contain growth factors, mRNA, microRNA and mitochondrial companents. This content ensures that the exosomes are long-acting [42][43][44].. MSCs are nonhematopoietic multipotent stromal cells that can be isolated from different sources, including bone marrow, adipose tissue, umbilical cord tissue, cord blood, placenta, dental pulp and amniotic fluid [12,45,46]. Umbilical cord Wharton's jelly derived mesenchymal stem cells (WJ-MSCs) are superior to other cell types in retinal degeneration in terms of how easily we can obtain these cells, as well as their tissue compatibility, rapid proliferation, long-term efficacy in the transplanted tissue, high paracrine effect, immunomodulation effect, non-tumoral side effect, and because these cells have similar features as the retinal pigment epithelium [13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…WJ-MSCs also undergo less nuclear and mitochondrial mutations compared to MSCs collected from adult tissues. WJ-MSCs do not stimulate T-cell proliferation because they do not express MHC class II [45,46].. WJ-MSCs have an effect on activated macrophages, reducing the secretion of inflammatory factors [12][13][14][15][16][17][18][19][20][21]. MSCs secrete factors that support cell survival and regulate adjacent cells in damaged tissue; hence, they can rescue the damaged naive nature of MSCs derived from an umbilical cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several types of stem cells have been subjected to clinical trials ( 106 ). Stem cells derived from the human placenta have been reported to be in clinical trials for a variety of therapeutic applications ( 107 ). In a single-center, non-randomized, intravenous dose-escalation phase Ib trial, patients with idiopathic pulmonary fibrosis received intravenous administration of placental MSCs from unrelated donors.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…MSCs are a class of cells originating in the mesoderm, including bone marrow MSCs and adipose MSCs, etc. Human umbilical cord MSCs (hucMSCs) are one of the important sources of MSCs [4,5], and they have strong proliferation and low immunity. Studies have reported that MSCs have homing effect on tumours such as glioma and ovarian cancer, and have anti-tumour effect on blood cancer and breast cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%